Возможности применения аморфных сталей в индуктивных датчиках тока - Павленко, Татьяна Павловна; Токарь, Максим Николаевич (НТУ "ХПИ", 2014)
В статье проведен анализ существующих технических решений, способствующих повышению эффективности использования датчиков тока за счет использования в магнитопроводах традиционных магнитомягких материалов и аморфной стали. Проведенные исследования показали возможность применения аморфной стали в сердечниках магнитопроводов индуктивных датчиков тока. Данное решение способствует экономии энергоресурсов и материалов магнитопроводов.

In the article the analysis of existing technical solutions, which increased to increased efficiency of current sensors due to the use in magnetic cores, traditional soft magnetic materials. The peculiarity of these sensors is their non contact design make-numbers that requires no mechanical influence, and they work by changing the e-electromagnetic fields. Main construction elements of inductive sensor are about-coil inductance and magnetic system, representing a magnetic circuit with a mobile element (anchor, core), which performs a linear or angular displacement under the action of the measured value. The main parameter of such sensors is the lineless and continuity features, which reaches application of materials with good-mi magnetic properties. The aim of the research is the definition of the properties and possible applications of amorphous steel in inductive current sensors.
Possible applications of amorphous alloys in induction current sensors
Keywords: сердечник; магнитопровод; датчик тока; аморфная сталь; индуктивность; core; magnetic circuit; current sensor; amorphous steel; inductance